#### Answer

$b=-\dfrac{3}{2}$

#### Work Step by Step

Using the properties of equality, the solution to the given equation, $
3b-2=7b+4
$, is
\begin{array}{l}
3b-7b=4+2
\\\\
-4b=6
\\\\
b=\dfrac{6}{-4}
\\\\
b=-\dfrac{3}{2}
.\end{array}
CHECKING:
\begin{array}{l}
3\left( -\dfrac{3}{2} \right)-2=7\left( -\dfrac{3}{2} \right)+4
\\\\
-\dfrac{9}{2}-2=-\dfrac{21}{2}+4
\\\\
-\dfrac{9}{2}-\dfrac{4}{2}=-\dfrac{21}{2}+\dfrac{8}{2}
\\\\
-\dfrac{13}{2}=-\dfrac{13}{2}
\text{ (TRUE)}
.\end{array}
Hence, the solution is $
b=-\dfrac{3}{2}
$.